Enlightening the Mechanism of Ferroptosis in Epileptic Heart - Akyüz, Enes; Saleem, Qamar H.; Sari, çiğdem; Auzmendi, Jeránimo; Lazarowski, Alberto (Current Medicinal Chemistry, 2024)
Epilepsy is a chronic neurological degenerative disease with a high incidence, affecting all age groups. Refractory Epilepsy (RE) occurs in approximately 30-40% of cases with a higher risk of sudden unexpected death in epilepsy (SUDEP). Recent studies have shown that spontaneous seizures developed in epilepsy can be related to an increase in oxidative stress and reactive oxygen derivatives (ROS) production. Increasing ROS concentration causes lipid peroxidation, protein oxidation, destruction of nuclear genetic material, enzyme inhibition, and cell death by a mechanism known as “ferroptosis” (Fts). Inactivation of glutathione peroxidase 4 (GPX4) induces Fts, while oxidative stress is linked with increased intracellular free iron (Fe+2) concentration. Fts is also a non-apoptotic programmed cell death mechanism, where a hypoxia-inducible factor 1 alpha (HIF-1α) dependent hypoxic stress-like condition appears to occur with accumulation of iron and cytotoxic ROS in affected cells. Assuming convulsive crises as hypoxic stress, repetitive convulsive/hypoxic stress can be an effective inducer of the “epileptic heart” (EH), which is characterized by altered autonomic function and a high risk of malignant or fatal bradycardia. We previously reported that experimental recurrent seizures induce cardiomyocyte Fts associated with SUDEP. Furthermore, several genes related to Fts and hypoxia have recently been identified in acute myocardial infarction. An emerging theme from recent studies indicates that inhibition of GPX4 through modulating expression or activities of the xCT antiporter system (SLC7A11) governs cell sensitivity to oxidative stress from ferroptosis. Furthermore, during hypoxia, an increased expression of stress transcriptional factor ATF3 can promote Fts induced by erastin in a HIF-1α-dependent manner. We propose that inhibition of Fts with ROS scavengers, iron chelators, antioxidants, and transaminase inhibitors could provide a therapeutic effect in epilepsy and improve the prognosis of SUDEP risk by protecting the heart from ferroptosis.
Keywords: Refractory epilepsy